Androgojik Yaklaşımlar Çerçevesinde Kurumsal Akademilerin Türkiye'de Konumlandırılması - Deveci, Tanju; Tezcan, Fatma (İstanbul Kültür Üniversitesi / Eğitim Fakültesi, 2017)
This paper provides a comparison of andragogical and pedagogical orientations to learning, and argues that andragogy needs to be viewed as a principle for lifelong learning. Andragogical and lifelong learning assumptions are discussed from the perspective of engineering education in general and project-based learning in particular. The paper also presents the results of a small-scale study conducted on fifty-eight freshman engineering students’ andragogical and lifelong learning orientations in the context of Khalifa University of Science and Technology, Petroleum Institute, Abu Dhabi in the UAE. Results showed that the students had a greater tendency towards andragogical orientations, and that they had a moderate level of lifelong learning orientation. Data also revealed a positive correlation between andragogical and lifelong learning tendencies, and a negative correlation between pedagogical and lifelong learning tendencies. The results of the study are discussed and recommendations are made.

Bu çalışma, öğrenmeye andragojik ve pedagojik yönelimlerin karşılaştırmasını ortaya koymakta ve andragojinin yaşamboyu öğrenme için bir ilke olarak görülmesini savunmaktadır. Yaşamboyu öğrenme ve andragojik varsayımlar genelde mühendislik eğitimi ve özelde de proje tabanlı öğrenme perspektifinden tartışılmaktadır. Çalışmada ayrıca, Abu Dhabi UAE’de Khalifa Bilim ve Teknoloji Üniversitesi’nde elli sekiz mühendislik öğrencisinin andragojik ve yaşamboyu öğrenme yönelimleri üzerine yapılan küçük ölçekli bir çalışmanın sonuçları sunulmaktadır. Araştırma sonuçları öğrencilerin andragojik yönelimlere daha fazla eğilimli olduklarını ve yaşamboyu öğrenme yöneliminde orta düzey olduklarını göstermiştir. Araştırma verilerinde, andragojik ve yaşamboyu öğrenme eğilimleri arasında pozitif bir ilişki olduğu; pedagojik ve yaşamboyu öğrenme eğilimleri arasında ise negatif bir ilişki olduğu ortaya çıkmıştır. Çalışmadan elde edilen bulgular tartışılmış ve öneriler geliştirilmiştir.
Birinci Sınıf Mühendislik Öğrencilerinin Proje Tabanlı Bir Dersteki Andragojik, Pedagojik ve Yaşamboyu Öğrenme Eğilimleri
Keywords: Andragogy; Pedagogy; Lifelong Learning; Project-based Learning; Engineering Education; Andragoji; Pedagoji; Yaşamboyu Öğrenme; Proje Tabanlı Öğrenme; Mühendislik Eğitimi